EFEKTIVITAS PENGELOLAAN NPL (NON PERFORMING LOAN) DI LEMBAGA PERKREDITAN DESA (LPD) - I Komang Dedy Saputra; Ni Luh Eka Ayu Permoni (Fakultas Ekonomi Dan Bisnis Universitas Palangka Raya (UPR), 2021)
This study aims to analyze the effectiveness of the management of Non-Performing Loans (NPLs) in the Pedawa Traditional Village LPD through the Non Performing Loan (NPL) ratio, Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Earning Asset Quality (KAP) and Cost. Operational Operating Income (BOPO), the sample used in this study is financial reports for 36 months. The research was conducted using quantitative analysis methods. The results of this study explain that the Capital Adequacy Ratio (CAR) has a significant negative effect on Non-Performing Loans (NPL), and Loan to Deposit Ratio (LDR), Earning Asset Quality (KAP), and Operational Income Operational Costs (BOPO) have a significant effect. positive for Non Performing Loans (NPL)